Climatic adaptation of species and varieties of grass and clover in the West Nordic countries and Sweden - Guðni Þorvaldsson 1952-; Liv Østrem; Linda Öhlund; Þóroddur Sveinsson 1956-; Sigríður Dalmannsdóttir 1969-; Rólvur Djurhuus; Kenneth Høegh; Þórdís Anna Kristjánsdóttir 1953- (2015)
Rit LbhÍ nr. 50 Eight experiments with monoculture of 24 varieties of grass and clover species and one mixture of two grass species and two clover species were established in the Faroe Islands (Kollafjørður), Greenland (Upernaviarsuk and Qassiarsuk), Iceland (Korpa and Möðruvellir), Norway (Fureneset and Holt) and Sweden (Lännäs). The main goal of this project was to evaluate important forage species and varieties, in terms of yield, persistence and adaptation to variable climate in the West Nordic countries. Timothy had on average the highest cover after three years in the experiments (63%) together with Knut, a smooth meadow grass variety (67%). Perennial ryegrass had the lowest cover after three years, or 28%. Meadow fescue had a similar cover as timothy in Iceland and Sweden and cocksfoot a similar cover as timothy in Iceland, Sweden and Fureneset. On average cocksfoot (Laban) and timothy varieties related to Grindstad gave the highest yield, 8.85 and 8.71 t/ha, respectively. These species were followed by tall fescue (Swaj), festulolium, perennial ryegrass, northerly timothy varieties and meadow fescue, yielding 8.51, 8.47, 8.23, 8.18 and 7.98 t/ha, respectively. Smooth meadow grass and common bent grass had lower yields, 7.52 and 7.30 t/ha, respectively. The results from these experiments show that we have a wide range of species and varieties usable in the West Nordic areas. We can meet an increase in temperature to a certain level by moving the more southern species and varieties farther north but this can be limited because of factors such as day length requirements or tolerance to diseases. Our most winter hardy varieties are still important to maintain. If the climate changes in the opposite direction these winter hardy varieties could be valuable for other areas as well. Nordic Atlantic Cooperation